2012
DOI: 10.1093/jac/dks355
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of antibiotic use in the community and challenges of antibiotic surveillance in a lower-middle-income country setting: a repeated cross-sectional study in Vellore, south India

Abstract: Patterns of antibiotic use varied across health facilities, suggesting that interventions should involve all types of health facilities. Although challenges were encountered, our study shows that it is possible to develop surveillance systems in LMICs and the data generated may be used to plan feasible interventions, assess impact and thereby contain resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 19 publications
3
73
1
Order By: Relevance
“…A survey conducted in South India showed that among 52,788 outpatients about 40.9% were prescribed with antibiotics (Chandy et al, 2013) but here in Bangladesh in this study 54.36% of outpatients were ordered with antibiotics (Table 1) which is significantly higher than India. Fluoroquinolones and penicillins were widely used antibiotics in South India and cephalosporins were more often used in urban private hospitals (Chandy et al, 2013). Another survey conducted on outpatients in Nepal had shown that 46.1% patients were male and 53.9% female (Lamichhane et al, 2006).…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…A survey conducted in South India showed that among 52,788 outpatients about 40.9% were prescribed with antibiotics (Chandy et al, 2013) but here in Bangladesh in this study 54.36% of outpatients were ordered with antibiotics (Table 1) which is significantly higher than India. Fluoroquinolones and penicillins were widely used antibiotics in South India and cephalosporins were more often used in urban private hospitals (Chandy et al, 2013). Another survey conducted on outpatients in Nepal had shown that 46.1% patients were male and 53.9% female (Lamichhane et al, 2006).…”
Section: Discussioncontrasting
confidence: 58%
“…Cephalosporin usage is highest in urban hospitals and pharmacy shops in India than rural hospitals (Chandy et al, 2013). A survey conducted in South India showed that among 52,788 outpatients about 40.9% were prescribed with antibiotics (Chandy et al, 2013) but here in Bangladesh in this study 54.36% of outpatients were ordered with antibiotics (Table 1) which is significantly higher than India. Fluoroquinolones and penicillins were widely used antibiotics in South India and cephalosporins were more often used in urban private hospitals (Chandy et al, 2013).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Rural hospitals used co-trimoxazole more often and urban private hospitals used cephalosporins more often; 41.1% of antibiotic prescriptions were for respiratory infection. 13 Pasha et al in their study reviewed 250 cases to evaluate the prescribing pattern of antibiotics in the treatment of various types of infection found that majority of the patients were treated with Quinolones (36.55%), the major route of drug administration employed was oral route. The most common were ciprofloxacin, amoxicillin, metronidazole, ampicillin, aminoglycosides, macrolide antibiotics, cephalosporin and sulphonamides.…”
Section: Discussionmentioning
confidence: 99%